THE PRESERVATION OF VARIOUS JOKO TINGKIR STORIES AS THE STRATEGY OF DEVELOPING FOLKLORE-BASED TOURISM - Elen Inderasari; Dwi Kurniasih (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2020)
Tourism recently becomes a priority in which the Indonesian government has strived to develop to increase domestic income. One of the interesting types of tourism is cultural tourism which has developed widely in the form of literary tourism. This paper aims to discuss how the preservation of the variation of Jaka Tingkir’s story can be a strategy in developing folklore-based literary tourism. In the practical effect, this paper tries to contribute ideas to the local government especially in Surakarta to find a proper strategy in developing a folklore-based as well as historical-based tourism. The results of the research show that in the preservation of folklore in a society, it is necessary to tell folklore with various emphasis contained in the story. This paper finds that Jaka Tingkir folklore needs to be preserved by maintaining its various versions of the story, such as the story of Jaka Tingkir and the crocodile, Jaka Tingkir and Kebondanu, the story of Jaka Tingkir and the heirloom of Kiai Bajugiling, Jaka Tingkir and Javanese philosophy, and the tomb of Jaka Tingkir as an imprint of the king of Pajang. These various stories about Jaka Tingkir contain some religious, historical, moral, heroic, faith, and worship values which are very important to comprehend in the society living with the story. The strategies used in developing literary tourism in Bengawan Solo which bases on Jaka Tingkir folklore include the tradition of larung gethek of Jaka Tingkir, Jaka Tingkir haul at his tomb in Pajang, Surakarta, and religious and literary tourism.